If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + (-2) = -5 3a + -2 = -5 Reorder the terms: -2 + 3a = -5 Solving -2 + 3a = -5 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3a = -5 + 2 Combine like terms: -2 + 2 = 0 0 + 3a = -5 + 2 3a = -5 + 2 Combine like terms: -5 + 2 = -3 3a = -3 Divide each side by '3'. a = -1 Simplifying a = -1
| -27+17+(-1)= | | 2a+3c= | | 2x+(-4)=14 | | 4.5x+13.5=2.5-x+3 | | -3z+8=35 | | 25x+63x-x=40 | | -2y+5=25 | | m+7m-7m-2= | | 126+43h=53.5h | | -6(-5+5b)-8b= | | 100x-1/2=0 | | 3z+(-9)=-9 | | 9x+14y=33 | | 2x^4-2x=0 | | w+71=6(3-w)+7w+53 | | 6x+56=2x+80 | | e-14.4=-20.8 | | n+11.5=-29 | | 7x-46=3x+30 | | 7(4+3)= | | 9x-74=4x-14 | | -266=7(8n-6) | | 7p+8q=54 | | b+0.6=1 | | c-16=41 | | -1.6+2p=3.8 | | 4(8u+8)-u=21(3u-9)+92 | | 5x+53+8x-55=180 | | 6x^2+41x= | | 3a^3+3ab^2+7a^2b+7b^3=0 | | -r-3(r-1)= | | 7p+3q=4 |